Improving Digital Literacy in Islamic Religious Education Through Tiktok Application - Mawadatul Af’idati; Budi Pangastuti; Rismawati Rismawati; Siti Roudhotul Jannah (Journal of Research in Islamic Education, 2025)
The advancement of digital technology demands a transformation in the education system, including in the teaching of Islamic Religious Education (IRE). This study aims to explore the effectiveness of using the TikTok application as a learning medium to enhance students’ digital literacy. Employing a descriptive qualitative approach and a case study method, data were collected through observation, interviews, and content analysis of student-created educational videos uploaded on TikTok. The findings reveal that TikTok usage increases students’ learning motivation, active participation, and critical thinking skills in understanding Islamic values. TikTok functions not only as an entertainment platform but also as an effective medium for fostering students’ religious character through creative da'wah content. Despite technical challenges such as audio issues and time limitations, innovative and relevant pedagogical strategies are crucial to optimizing TikTok’s potential in education. Therefore, integrating digital media into IRE learning represents a transformative approach that supports the achievement of 21st-century competencies.